A Method to Increase the Frequency Stability of a TCXO by Compensating Thermal Hysteresis - Zhaoyang Wang; Jie Wu (Sensors, 2020)
Due to the rapid growth of electronic information technology, the need for the higher stability of crystal oscillators has increased. The temperature-compensated X’tal (crystal) oscillator (TCXO), a type of crystal oscillator with high frequency stability, has been widely used in communications, sensor networks, automotive electronics, industrial control, measuring devices, and other equipment. The traditional TCXO only performs frequency compensation based on the current temperature, without considering the error caused by thermal hysteresis. As the frequency stability of the TCXO improves, the thermal hysteresis of the crystal oscillator has a negligible influence on the frequency stability of the crystal oscillator. This study measured different compensation tables for hysteresis curves at different temperatures and used a microprocessor to store the historical information of crystal temperature changes. Furthermore, corresponding algorithms were designed to select the correct values, according to the temperature change history, to compensate for the thermal hysteresis of the crystal oscillator error. Experiments show that this method can reduce the hysteresis error of the crystal oscillator from 700 to 150 ppb (−40 to 80 °C).